1981
DOI: 10.5006/1.3577538
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Inhibiting Action of Benzene Thiols and Related Compounds on the Corrosion of Zinc in Acidic Media

Abstract: The effect of benzenethiol and its methyl, amino, and carboxylic ring substituted derivatives, benzylthiol and thioglycollic acid on the electrochemical and corrosion behavior of zinc in CH3000H, H2SO4, and HCI solutions was studied using the galvanostatic technique. In CH3000H, compounds which function by an adsorption mechanism were found to have inhibitive effects on the corrosion of zinc, while those functioning by surface chelation were ineffective. In H 2SO4 and HCI, with the exception of o-methylbenzene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…3 A comparative study of the inhibition efficiency (E) of some OATP derivatives on the corrosion of iron in hydrochloric acid (HCl) and of zinc and copper in acetic acid (CH 3 COOH) has been performed previously. [4][5] OATP and its dimer have been shown to be efficient inhibitors of corrosion and hydrogen hot air. The counter electrode was a cylindrical platinum grid with a large surface area.…”
Section: Methodsmentioning
confidence: 99%
“…3 A comparative study of the inhibition efficiency (E) of some OATP derivatives on the corrosion of iron in hydrochloric acid (HCl) and of zinc and copper in acetic acid (CH 3 COOH) has been performed previously. [4][5] OATP and its dimer have been shown to be efficient inhibitors of corrosion and hydrogen hot air. The counter electrode was a cylindrical platinum grid with a large surface area.…”
Section: Methodsmentioning
confidence: 99%
“…Corrosion inhibitors play an important role in controlling the corrosion of metals. Organic compounds studied as inhibitors include imidazole azo derivatives (Ekilik and Grigorev, 1973), thiourea (Shams El Din et al , 1977), benzene thiols and related compounds (Abdel et al , 1981), and Schiff bases of chloroanilines (Desai et al , 1995), and 2‐mercaptobenzimidazole (Wang et al , 2003a). In earlier work, inhibition of the corrosion of zinc in sulphuric acid by Schiff bases of ethylenediamine (Shah et al , 2004), ortho‐substituted aniline‐N‐salicylidenes (Desai et al , 2003), meta‐substituted aniline‐N‐salicylidenes (Talati et al , 2005a), Schiff bases of ethylenediamine/triethylenetetramine with salicylaldehyde (Desai et al , 2008), has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature reveals that there are very few substances that may be considered as highly efficient inhibitors for zinc in non‐oxidizing acids, particularly sulphuric acid. Compounds studied as inhibitors include, benzaldehyde and its derivatives (Grigorev and Ekilik, 1969), quinoline derivatives (Kawai et al , 1971), quaternary salts of pyridine bases (Antropov et al , 1971), alkaloids (Subramanyan and Ramkrishnaiah, 1973), imidazole azo derivatives (Ekilik and Grigorev, 1973), thiourea (Shams El Din et al , 1977), benzene‐thiol and related compounds (Abdel Aal et al , 1981), Schiff bases of chloroanilines and toluidines (Desai et al , 1990) and 2‐mercaptobenzimidazole (Wang et al , 2003). In earlier work, the inhibition of corrosion of zinc in sulphuric acid by Schiff bases of ethylenediamine (Shah et al , 2004), ortho‐substituted aniline‐N‐salicylidenes (Desai et al , 2003), ortho‐, meta‐, and para‐aminophenol‐N‐salicylidenes (Talati et al , 2005a, b), and meta‐substituted aniline‐N‐salicylidenes (Talati et al , 2005a, b), has been reported.…”
Section: Introductionmentioning
confidence: 99%